Technology-Based Learning Systems In Supporting Learning And Teaching Processes In Islamic Boarding Schools - Ilham Akbar; Fauziyah Adzimatinur (SOCIRCLE : Journal Of Social Community Services, 2022)
Salah satu factor yang dapat meningkatkan efektivitas pembelajaran online adalah Guru yang telah menguasai pengelolaan kelas secara online. Pengelolaan kelas ini mencakup materi yang relevan, cara penyampaian materi, infrastruktur yang dibutuhkan untuk kelas online, serta bagaimana siswa dapat mengakses kelas dan mempelajari apa yang disampaikan sesuai dengan fasenya masing-masing. Sosialisasi yang diberikan kepada guru ini diharapkan dapat memberikan pemahaman mengenai cara membuat dan memberikan materi dengan fasilitas online yang dapat membantu pembelajaran dari manapun dan kapanpun. Beberapa platform yang digunakan dalam belajar online ini adalah YouTube, Zoom, Google Meeting, dan Google Classroom. Pada umumnya, guru dapat memahami tata cara melakukan pertemuan dan membuat materi, serta menggunggahnya agar dapat diakses oleh siswa. Namun, beberapa kendala ditemukan pada guru yang mengajar mata pelajaran dengan konsep hitungan, misalnya matematika, kimia, fisika. Hal ini dikarenakan terbatasnya fasilitas yang diperlukan untuk memberikan contoh perhitungan layaknya ketika guru menerangkan di papan tulis. Abstrack One factor that can increase the effectiveness of online learning is teachers who have mastered online classroom management. Management of this class includes relevant material, how to deliver the material, the infrastructure needed for online classes, and how students can access the class and learn what is delivered according to their respective phases. The socialization given to teachers is expected to provide an understanding of how to create and provide material with online facilities that can help learning from anywhere and anytime. Some of the platforms used in online learning are YouTube, Zoom, Google Meeting, and Google Classroom. In general, teachers can understand the procedures for conducting meetings and creating materials, as well as uploading them so that they can be accessed by students. However, some obstacles were found in teachers who teach subjects with the concept of calculation, for example mathematics, chemistry, physics. This is due to the limited facilities needed to provide examples of calculations like when the teacher explains on the blackboard.